Age-Related Alterations in Endothelial Function of Femoral Artery in Young SHR and WKY Rats. (20th March 2014) - Puzserova, Angelika; Ilovska, Veronika; Balis, Peter; Slezak, Peter; Bernatova, Iveta
Abstract : The present study was designed to evaluate the effects of vascular aging in juvenescence on endothelial function in femoral arteries and to assess differences between normotensive and hypertensive rats. The aim of the study was to determine if age affected nitric oxide- (NO-) mediated relaxations in normotensive and hypertensive rats. Juvenile (7-week-old) and young adult (22-week-old) male Wistar-Kyoto (WKY) and spontaneously hypertensive rats (SHR) were used in this study. Femoral artery (FA) reactivity was determined by wire myograph and NO synthase activity by conversion of [ 3 H]-L-arginine. During juvenescence systolic blood pressure (tail-cuff) increased significantly only in SHR, while NO synthesis decreased significantly in both strains. Endothelium-dependent relaxations to acetylcholine were reduced in the FA of SHR compared to age-matched WKY at both ages, yet these parameters were unchanged in adult rats compared with juvenile animals. The NO-dependent component of vasorelaxation was markedly reduced, whereas the NO-independent component was increased in adult compared to juvenile rats in both strains. The endothelial dysfunction in SHR at both ages was associated with reduction of NO-independent mechanisms. In conclusion, aging in early periods of life was associated with reduction of vascular NO production and bioavailability in both strains investigated. This reduction was however fully compensated by accentuation of NO-independent mechanisms.